The hour of peril : the secret plot to murder Lincoln before the Civil War - Stashower, Daniel (Minotaur Books, 2013)
Two-time Edgar award-winning author Daniel Stashower uncovers the riveting true story of the "Baltimore Plot," an audacious conspiracy to assassinate Abraham Lincoln on the eve of the Civil War.